Family values reflecting the specifics of the nation (Eurasian Journal of Philology Science and Education, 2020)
This article describes the importance of family values. Also highlighting the merits of each familymember in family life, describes the basic obligations of parents in the upbringing of children andtheir role in the family. Considers the basic values inherent in the Kazakh family, which are realizedon the basis of national values and the impact of family education on society. We all know that themain value in the family is the upbringing of the young generation, accordingly considers generically the upbringing of the young generation and shows that the upbringing itself consists of severalsmall values. Analyzing this topic, article defines the concept of family values. The family is the mainteacher of personality. It is in the family that a unique image of each child is created, creating him asa person. On the basis of Kazakh proverbs, the process of forming a family structure is consistentlyjustified, the main functional parameters of the family are highlighted, family values are formulatedand listed. Customs and traditions, proverbs, sayings inherent in the Kazakh people do not have aneducational effect on their own, but they have educational effect under conditions where parentsfollow them as personal example in the family, support the principles and ideas expressed in them.Each saying, proverb, custom, at the correct application become a fine, instructive moral lesson foryounger generation.